Polyamines and inhibitors used in successive culture media for in vitro rooting in Berberis buxifolia - Arena, Miriam Elisabet (2005)
Although Berberis buxifolia has been reported to propagate in vitro, rooting is difficult to achieve during subcultures, with reduced quantity and quality of roots, as is the case with many other woody species. Several cofactors of rhizogenesis have been proposed, and the role of polyamines in rooting has recently acquired relevance. Polyamines can stimulate or inhibit microshoot rooting depending on the type and concentration of polyamine and rooting phase, while polyamine inhibitors can improve rooting in some cases. A study of the in vitro rooting of B. buxifolia using polyamines and a mix of polyamine inhibitors in a two-step culture medium is described here, in which a new successive rooting medium was successfully implemented. While polyamine inhibitors sometimes improved rooting, nutrient medium containing a low polyamine concentration (i.e., 1 μM) enhanced rooting compared with the control medium. The best micro-shoot rooting response resulted from the addition of 1 μM spermidine during the expression phase in the absence of inhibitors in both rooting phases. Overall, incorporating polyamine in the successive media enhances the quality and quantity of roots in B. buxifolia, thus confirming their role during the induction and expression of the radicle primordia differentiation.